Preservation of the environment for a healthy quality of life - Saraiva, Marcos José Cavalcanti Leite (Rev Rene, 2016)
Sanitarians have proclaimed that environment and quality of life are closely intertwined for a long time, but, recently, this awareness has become more visible due to the proliferation of infectious diseases and the increased number of deaths caused by environmental degradation.The aggression process against the environment started with the establishment of the large metropolitan areas, because the man has changed the ecosystem to ensure its own survival and provide comfort for itself. These transformations of the preexisting space for human habitation, in a disorderly manner, affected the characteristics of the Earth’s surface by destroying a huge part of the plant coverage, thereby resulting in abrupt climate changes, as well as in contamination of soil, atmospheric air, sea water, rainwater, river water andgroundwater